Abnormal Cerebral Perfusion and Functional Connectivity in Women with Overactive Bladder - Shichun Chen; Zongpai Zhang; Yakun Zhang; Kenneth Wengler; Steven Weissbart; Weiying Dai; Xiang He; Justina Tam (Brain Sciences)
Background: Overactive bladder (OAB) has been linked to abnormal cerebral blood flow (CBF) and functional connectivity (FC). However, findings related to CBF and FC changes in OAB remain inconsistent across the literature. Methods: This feasibility study employed arterial spin labeling (ASL) to investigate abnormal CBF and posterior cingulate cortex (PCC) FC in individuals with OAB, both at rest and during bladder filling. ASL images were collected from twenty-two female participants (twelve with OAB and ten healthy controls) at bladder filling volumes of 0, 50, 100, 200, 350, and 500 mL. For OAB participants, scans were obtained both at baseline and following a single-session treatment. ASL images were categorized into low-urge and high-urge conditions based on participants’ subjective urge rating during bladder filling. A flexible factorial design was implemented with three factors: subject, group (control, OAB at baseline, and OAB posttreatment), and urge state (low vs. high). Results: Compared to controls, OAB participants exhibited significant decreases in ΔCBF (high urge minus low urge) in the medial prefrontal cortex and increases in ΔCBF in the supramarginal region. Additionally, ΔPCC FC with the insula was reduced in OAB participants. Posttreatment, OAB participants showed increased ΔPCC FC with the postcentral and parietal (PocP), regions associated with the sensorimotor network. Notably, changes in ΔPCC-PocP FC were associated with improvements in OAB symptoms. Conclusions: These findings support the feasibility of using ASL to probe dysfunctional brain–bladder control mechanisms and treatment-related changes in OAB participants, highlighting the involvement of sensory processing and attention regulation in this condition.